Classification of hearing status and health- related quality of life of elderly people with presbycusis in South-West, Nigeria (2017)
"This study investigated the prevalence of the condition, and health-related quality of life of the elderly with presbycusis. Multi-stage sampling technique was employed to select 146 participants from four (4) south western states in Nigeria. The study was carried out, using Pure-tone audiometric test (PTA) to determine the prevalence and classification of the condition, while HHIE and MOS SF-36 scales were employed to investigate the perceived hearing communication specific problems and health-related quality of life of the participants. Data were analysed, using frequency counts and percentages. The findings reveal that presbycusis is a common disabling condition among the elderly (83.4%), and not peculiar to any gender (M=85.3%; F=80.8%). Also, the findings establish high level of socioemotional adjustment problems, poor social relationships and withdrawal syndrome, feelings of depression and loneliness, reduced daily living functions, poor general well- being and reduced quality of life among the elderly assessed. Therefore, it was recommended that detection and management of presbycusis and associated conditions be done early, while concerted efforts should be by all the stakeholders towards the prevention of presbycusis through comprehensive hearing conservation strategies and promotion of improved quality of life of the elderly in the country"